The Factors Causing Absenteeism and Counseling Teachers Efforts to Overcome It in Man Kota Pariaman - Sakinah, Mawaddatus; Syukur, Yarmis (Universitas Negeri Padang, 2023)
Ditching behavior is one of the deviant behaviors carried out by students at school which will harm the students themselves. Skipping school is a behavior that is classified as maladaptive, an act of violating school rules that is carried out without thinking about the impact or consequences that will occur in the future. This research is a qualitative research with a case study approach. There were 9 research respondents, 3 truant behavior subjects, 3 counseling teacher subjects and 3 truant student informants using a porposive sampling technique. The instruments used in this study were interview guides, observations, and documentation studies, while data analysis was carried out in 3 steps, namely: 1) data reduction (data reduction), 2) data exposure (data display), 3) drawing conclusions and verification ( conclusion drawing/verifying). The results of the study revealed that the causes of truant behavior that occurred at MAN Kota Pariaman were more dominated by the first, the high feeling of laziness possessed by the students themselves, the second, the low motivation in learning, the third, rarely making and collecting assignments, the fourth, the background of a broken home family and lack of attention from family, fifth easily influenced by friends. Efforts made by BK teachers to overcome truancy behavior, namely by preventing providing information services and overcoming them with individual counseling services.